TEN CONSIDERATIONS ABOUT THE DEMOGRAPHIC SITUATION OF DEVELOPING COUTRIES - Antonio Carolino Gonçalves (Tópicos Educacionais)
Considers the demographic situation of developing countries, whose problems must find solutions based on its historical, economical, social and political realities.